La presencia de los nahuatlismos en el español de México desde un enfoque diacrónico - Petkova, Ingrid (Acta Hispanica, 2017)
The aim of this article is, on one hand, to talk about the language contacts between Mexican Spanish and the indigenous languages of Mexico, more specifically Nahuatl; on the other hand, to introduce the linguistic phenomenon of Nahuatl loanwords and their presence in the Mexican literature from diachronic point of view.